Assessing the diesel engine performance using piston with dissimilar material piston rings. (2020) - Karikalan, L.; Sakthivel, P.
Abstract: Investigation displays that frictional loss in an I.C engine is the utmost important aspect in defining the fuel frugality and performance of an automobile. The behavior and transient friction features of a piston ring with dissimilar materials are assessed experimentally by an engine device. Outcomes are stated for a sequence of tests on piston rings with dissimilar groupings of dissimilar material. Evaluations were provided among three dissimilar kinds of materials for piston rings. A combination of the toroidal piston with aluminium-titanium piston ring has better performance over the other combination.